A Study of the Influence of Corporate Culture and Organizational Design on Entrepreneurship Orientation and Employee Performance in the Largest Health Laboratory Company in Indonesia - Astuti Rah Diati; Okder Pendrian (Jurnal Multidisiplin Sahombu, 2025)
The Largest Health Laboratory in Indonesia divides the organization into 3 levels, Head Office, Regional Office, and Branch Office. To be able to encourage various innovation initiatives related to digitalization which is believed to help the Largest Health Laboratory in Indonesia to quickly adapt to changes, especially in the digital era. This study aims to determine whether there is a relationship between the influence of Corporate Culture and organizational design on Entrepreneurial Orientation and employee performance at the Largest Health Laboratory in Indonesia. The research method is a quantitative method by distributing questionnaires to respondents. The sample in this study amounted to 200 respondents. The data analysis method uses Structural Equation Modeling with a Partial Least Square (SEM-PLS) approach. The results of the study indicate that corporate culture and organizational design variables have a positive and significant effect on entrepreneurship orientation and employee performance.